Risk factors for burnout in the preparation of student final projects - Weni Sia’tang; Kens Napolion; Andi Anugrah Oktaviani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Burnout is a condition when someone feels exhausted from doing something. An individual at risk of burnout feels stress as the onset and prolonged fatigue. Aim: knowing the risk factors for burnout in the preparation of student final projects. Methods: the research employs the correlational quantitative design and the cross-sectional approach. The population was 274 students who had been writing the thesis. The sample was selected by using the quota sampling technique, and as many as 162 students were chosen to be included as the samples. The independent variables of the research were stress, family support, and peer support system; the dependent variable was burnout. The data were gathered by using 4 questionnaires that the respondents filled out. The analysis was conducted using chi-square (Pearson Chi-Square), and the significance level was = 0.05. Results: The result shows that stress significantly correlates with burnout incidence in writing a thesis, where the value of p is p (0,000). Meanwhile, the family support confirmed its relationship by obtaining the value of p (0,003), and the peer support system also showed the value of p (0,003), which established the correlation between burnout and the student's thesis writing. Conclusion: The study shows the correlation of stress, family support, and peer support systems related to burnout risk. Further studies should include other variables such as workload, rewards, community, fairness, value ambiguity, and role conflict.